Politisasi Sertifikat Halal - Lutfi Rosyad Alfikri; Ahmad Fauzi (FISIP Universitas Malikussaleh, 2022)
Indonesia is a country that has a Muslim majority population, so there are many rules that are intended and specifically for Muslims, one of which is related to rules in food matters. The government in providing this service seeks to provide guarantees for halal food products for Muslim consumers through halal certificate instruments. This research is a literature study that analyzes the politicization of halal certificates in the MUI fatwa. A qualitative approach is used to analyze and interpret the MUI fatwa in granting halal certificates and the politics contained therein. The data was obtained from the publications of several journals and e-books that were accessed through Google Chrome and Google Scholar. Collecting data related to the MUI fatwa in halal labeling in its political aspect. This research procedure is carried out by means of a literature review. The data analysis process was carried out by reducing the data obtained from the search results of data from Google Chrome and Google Scholar. After reducing the data, it is presented in the form of a description to explain the politicization of the halal certificate in the MUI fatwa. The next step is to draw conclusions on the results of the analysis to produce new findings on the politicization of the MUI fatwa halal certificate. Halal certification issues are handled by 3 institutions namely MUI, Ministry of Health, and Ministry of Religion through the signing of a Joint Decree (SKB) of the three institutions in 1996. Halal certification is then regulated by various laws that bind it.Negara Indonesia merupakan negara yang memiliki penduduk mayoritas muslim sehingga banyak aturan yang ditujukan dan dikhususkan untuk orang muslim salah satunya yakni terkait aturan dalam masalah makanan. Pemerintah dalam memberikan layanan ini berikhtiar dengan cara memberikan jaminan produk makanan halal bagi konsumen muslim melalui instrumen sertifikat halal. Penelitian ini merupakan studi literatur yang menganalisis politisasi dalam sertifikat halal pada fatwa MUI. Pendekatan kualitatif digunakan untuk menganalisis dan menafsirkan fatwa MUI dalam pemberian sertifikat halal serta politik yang terkandung didalamnya. Data diperoleh dari pubikasi beberapa jurnal serta e-book yang diakses melalui google chroom maupun google scholar. Pengumpulan data terkait fatwa MUI dalam pelabelan halal dalam aspek politiknya. Prosedur penelitian ini dilakukan dengan kajian studi literatur. Proses analisis data dilakukan dengan mereduksi data yang diperoleh dari hasil pencarian data dari google chroom maupun google scholar. Setelah melakukan reduksi data disajikan dalam bentuk deskripsi untuk menjelaskan politisasi dalam sertifikat halal pada fatwa MUI. Selanjutnya yakni melakukan penarikan kesimpulan terhadap hasil analisis untuk menghasilkan temuan baru pada politisasi sertifikat halal fatwa MUI. Masalah sertifikasi halal ditangani oleh 3 lembaga yaitu MUI, Kementerian Kesehatan, dan Kementerian Agama melalui penandatanganan Surat Keputusan Bersama (SKB) tiga lembaga tersebut pada tahun 1996. Sertifikasi halal kemudian diatur dengan berbagai undang-undang yang mengikatnya.